Introduction to occupational therapy - O'Brien, Jane Clifford; Hussey, Susan M.; Sabonis-Chafee, Barbara (Elsevier/Mosby, 2012)
Offering an overview of the profession and the practice of Occupational Therapy (OT), this title prepares you for the roles, responsibilities, and relationships of the OT practitioner. It incorporates the advanced revisions of the Occupational Therapy Practice Framework, which defines the OT process and areas of concern